Industrial tribology sustainable machinery and industry 4.0 - Katiyar, Jitendra Kumar (CRC Press, Taylor & Francis Group, 2023)
Covering energy-saving technologies and how these are incorporated into component design, this book is relevant to many industries, including automotive engineering, and discusses the topical issue of sustainability in industry. This book details recent fundamental developments in the field of tribology in industrial systems.Tribology has advanced significantly in recent years. Tribological performance depends on external parameters such as contact pressure at the interface, system temperature, relative speed between bodies and contact behaviour. Through ensuring that mechanisms work in an energy-efficient manner and minimizing wear, engineers should seek to implement the study of tribology to improve the life of machinery within industry. Essential to the study of component design and condition monitoring, the book touches upon topics such as gears, bearings and clutches. Additionally, it discusses tribology’s relation to Industry 4.0 and incorporates the results from cutting-edge research.Industrial Tribology: Sustainable Machinery and Industry 4.0 will be of interest to all engineers working in industry and involved in mechanical engineering, material engineering, mechanisms and component design and automotive engineering.
Keywords: bicssc / Materials science; bicssc / Automotive technology & trades; bicssc / Engineering - general; bicssc / Product design; bicssc / Technical design; Industrie 4.0; Tribologie